2018
DOI: 10.1080/07481187.2018.1531088
|View full text |Cite
|
Sign up to set email alerts
|

Suicide ideation among Southern U.S. Sexual minority college students

Abstract: Sexual minority individuals are at higher risk for suicide ideation compared with heterosexual individuals. We tested whether the interpersonal-psychological theory of suicide explains increased suicide ideation among sexual minority college students living in the southeastern region of the United States. The cross-sectional study assessed correlates of suicide ideation in a convenience sample (n = 82) of sexual minority college students. Perceived burdensomeness and thwarted belongingness correlated with suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(61 reference statements)
3
11
0
Order By: Relevance
“…This suggests that perceived burdensomeness is a stronger risk factor for suicidal ideation than thwarted belongingness, at least among LGBTQ+ youth who utilized crisis services. These findings are generally consistent with previous cross-sectional studies of LGBTQ+ individuals, with some observing that perceived burdensomeness and thwarted belongingness were both associated with greater suicidal ideation (Grossman et al, 2016;Pate & Anestis, 2019;Plöderl & Fartacek, 2005;Ploderl et al, 2014;Wolford-Clevenger et al, 2020) and others observing that only perceived burdensomeness was associated with greater suicidal ideation (Baams et al, 2015(Baams et al, , 2018Woodward et al, 2014). Because of floor effects in perceived burdensomeness, it is possible that associations that involved perceived burdensomeness were attenuated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that perceived burdensomeness is a stronger risk factor for suicidal ideation than thwarted belongingness, at least among LGBTQ+ youth who utilized crisis services. These findings are generally consistent with previous cross-sectional studies of LGBTQ+ individuals, with some observing that perceived burdensomeness and thwarted belongingness were both associated with greater suicidal ideation (Grossman et al, 2016;Pate & Anestis, 2019;Plöderl & Fartacek, 2005;Ploderl et al, 2014;Wolford-Clevenger et al, 2020) and others observing that only perceived burdensomeness was associated with greater suicidal ideation (Baams et al, 2015(Baams et al, , 2018Woodward et al, 2014). Because of floor effects in perceived burdensomeness, it is possible that associations that involved perceived burdensomeness were attenuated.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the studies that have examined the IPTS among LGBTQ+ individuals have largely relied on cross-sectional data and focused on adults. Several studies have found that sexual minority adults report greater perceived burdensomeness than heterosexual adults (Hill & Pettit, 2012;Pate & Anestis, 2019;Woodward et al, 2014), and that both perceived burdensomeness and thwarted belongingness are associated with greater suicidal ideation among sexual minority adults (Hill & Pettit, 2012;Pate & Anestis, 2019;Plöderl & Fartacek, 2005;Ploderl et al, 2014;Wolford-Clevenger et al, 2020), as well as transgender and gender nonconforming youth and young adults (Grossman et al, 2016). However, some studies have found that only perceived burdensomeness is associated with greater suicidal ideation among sexual minority youth and adults (Baams et al, 2015(Baams et al, , 2018Woodward et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given SMs’ risk for discrimination, rejection, violence, and stigma (i.e., minority stress), SMs may be more likely to experience feelings of social disconnection (Wolford-Clevenger et al, 2018; Woodward et al, 2014). A sense of belongingness (feelings of emotional connection to and feelings of safety around others in a community; Yuval-Davis, 2006) may be difficult to achieve for SMs who participate in nonaffirming religions (Dahl & Galliher, 2012).…”
Section: Belongingness and Suicidal Ideationmentioning
confidence: 99%
“…SMs face unique stressors due to their minority status (Meyer, 2003). One of the most insidious SM stressors, HI, is potently related to both social alienation and SI (Gibbs, 2015; Meyer, 2003; Wolford-Clevenger et al, 2018). IH is experienced when SMs internalize negative messages regarding same-sex sexuality, leading to devaluation of the self (Gibbs, 2015).…”
Section: Belongingness and Suicidal Ideationmentioning
confidence: 99%
See 1 more Smart Citation